POSISI ULAMA DALAM PEMERINTAHAN KOTA PADANGSIDIMPUAN - Fikri, Sholeh (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2016)
This study aimed to get an overview of the position of ulama in the government of Padangsidimpuan City. The position of ulama must be considered by the government, because they are the potential elements of people who didnot all people have it. One thing to remembered is ulama as the partner of government. This is a descriptive research in which collecting the data through observation and interviews with ulama and Muslim scholars in the this city. The results indicated that the government had less attention to religious activity, except that routines such as MTQ, and activities during Ramadhan. Public welfare activities are not yet visible. The government's attention to the education sector which is a symbol of the city Padangsidimpuan also goes unnoticed. The roles of ulama seems still less in contributing to the development of this country, and the communication is not created because of needed. Because the minim roles, ulama maynot give the effect to the government; even, the government restraints from them.Â  The government just stay closer to ulama at the certain time, or if they have powerful effects in the society. Moreover, the way to communicate between ulama and societies is still traditionally, it is not in modern and accurate communication. It makes government didnot give big attention and appreciation to them; because they also have small function and contribution to the government.